Prevalence and associated factors for overweight and obesity in students of a private school in Sao Paulo - Coutinho, Renan Berteli; Fina Speretta, Guilherme Fleury [UNESP] (Inst Brasileiro Pesquisa & Ensino Fisiologia Exercicio-ibpefex, 2015)
Obesity has grown significantly in recent years, thus becoming a serious public health problem mainly because of excess fat increase the risk of developing several chronic degenerative diseases associated. The aim of this study was to investigate the prevalence of overweight and obesity in 134 children attending a private school in Sao Paulo - SP, 72 males and 62 females 06-10 years. To collect such data Index Body Mass (BMI) questionnaire Activity Level and exercise made by child beyond level Feed Same inside University activities were used. The prevalence of overweight and obesity was 41.8 % for girls, 42.9 % for boys and 42.5 % for the total sample. These results suggest that the values of overweight and obesity among schoolchildren in Sao Paulo SP were significant, and its prevalence is higher in male subjects. The implications that the results show us relate to the poor practice of physical activities and exercises, spending time with electronics and an inadequate diet, with a high frequency in restaurants fast foods. As intervention and prevention of obesity in childhood, enters the scene and school has a very important role in clarifying and guiding children to a more active life by encouraging the practice of physical activities and exercises and proper nutrition. For the results to be most effective you must have a multidisciplinary team consisting of physical educators, nutritionists, physicians, psychologists, etc.
Keywords: Children; Exercise; Food; School